Are Pandemics Bad for Business? Evidence From the US COVID-19 Experience (2021)
The economic downturn caused by the COVID-19 contingency cannot be denied. Many authors have studied the effects of the sanitary emergency on labor force and the demand and supply of goods and services. This paper aims to understand the consequences of the shock to the economy caused by the pandemic, measured through mobility restrictions, in the business context. Using Google Mobility and The New York Times report, stay-at-home orders were used as a proxy for mobility restrictions. The effect of said restrictions on initial unemployment benefit claims and new business applications provides an insight into the change in people’s livelihoods. The difference-in-differences and event study methodologies were applied with data from 2010 to the third week of August 2020. The results indicate that the restrictions on mobility had a significant impact on both outcome variables. The effect on unemployment claims was still present at the time of this paper, while the behavior of new business applications was mostly affected for the first few weeks and then had a quick rebound.